Tier II MRV of livestock emissions in China - Final report & Annexes - Dong, Hongmin; Zhu, Zhiping; Li, Yu’e; Wei, Sha; Zhang, Yu; Wollenberg, Eva Karoline; Wilkes, Andreas; Ma, Cuimei; Wang, Tian; Wang, Jiancheng; Pickering, Andrea; Leahy, Sinead (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Countries are required to account for greenhouse gas (GHG) emissions and their mitigation under the UNFCCC’s Paris Agreement, yet most countries are still developing their systems for the measurement, reporting and verification (MRV) of emissions in agriculture. Guidance from the IPCC exists to estimate impacts, yet implementation of MRV also requires tailoring to country needs and conditions. In the livestock sector, accurate, comparable, consistent, complete and transparent MRV systems that can capture changes in emissions and sequestration from a range of practices and agroecological conditions are essential to guide the transformation to a low emissions future. Many countries with livestock emissions are seeking advanced GHG accounting to better reflect national circumstances and track mitigation due to productivity changes. To help countries improve accounting, CCAFS and experts across the globe are working together with countries to identify cost-effective technically sound MRV and the guidance, tools, and platforms that support them. As part of its national accounting, China is now seeking to improve their MRV of emissions from livestock. This project supports that effort. The purpose of this study is to develop methods and systems for Tier II MRV of livestock emissions at provincial level (Hebei Province) in China. - The objectives of this project are: (1) Produce practical guidance; (2) Build capacity for Tier II MRV among province-level authorities; (3) Develop methods and that can be used to support Tier II MRV elsewhere.